Narrative inquiry of language assessment literacy development of pre-service English as a foreign language teacher in China - Juanjuan, Geng (2023)
As an indispensable element in the teaching and learning, assessment not only informs teachers about the effectiveness of the instruction, but also frames student learning. However, pre-service English as a Foreign Language (EFL) teachers across the world have been suggested to possess an inadequate level of language assessment literacy (LAL). The first step is to understand their concerns in LAL. To address the paucity, this narrative inquiry is conducted to explore pre-service EFL teachers’ LAL conceptualizations, self-evaluated proficiency level, evolvement trajectories, and the mediating factors in the evolvement process. Six participants from a pre-service EFL teacher education programme in China were purposefully sampled. The narrative interviews, assessment artifacts, and journals were collected and analyzed by narrative analysis and thematic analysis. The findings showed that the participants conceptualized LAL as a scaled eight-dimensional concept embedded in the social-cultural contexts. They tend to self-evaluate their LAL proficiency ranging from insufficiently qualified, through marginally qualified, to satisfactorily qualified. Besides, the experiential, contextual, and personal mediating factors were identified to participate in LAL evolvement. From bottom-up, the mediating factors participated in constructing pre-service EFL teachers’ knowledge base, shaping their assessment conceptions, filtering the assessment practices, and facilitating the assessor identity construction. With the enhanced LAL, they were more attentive to reflect on the influence of these mediating factors. As to the LAL evolvement trajectory, all the participants went through three mastery levels from the first assessment knowledge base through internalized assessment understanding to assessor identity construction. This study contributes to LAL conceptualization by involving in the neglected stakeholders, pre-service EFL teachers and enriches the application of narrative inquiry in LAL field. The findings can be used as a guidance for the improvement of deficient LAL among pre-service EFL teachers by offering implications for the teacher educators and teacher preparation programmes.